ANALISIS PERSEDIAAN PRODUK FARMASI CAIRAN INFUS PADA PEDAGANG BESAR FARMASI (PBF) PT. DOS NI ROHA SAMARINDA - Nuriansyah Nuriansyah; Istimaroh Istimaroh (Jurnal Ekonomi dan Manajemen, 2018)
This Research aims to knows the amount of supply of liquid infuse as the pharmaceutical product as most efficient at PT. Dos Ni Roha Samarinda. Analyser used the method of Economic of Order Quantity (EOQ).The Result by ordering for Ecosol Ringer Lactated (RL) as much 10 times and as much 9.818 bottle, 9 times and NaCl of 8,874 bottles and 10 times for Gelofusine of 297 bottles ordering in one year and each time order with the expense by equal to Rp. 16.494.309, Rp. 12.199.695, Rp.17.618.480 and Reorder point where company have to order to return at the time of stock reminded by 6.025 bottle, 4.777 bottle and 301 bottle.